Dimension of Mutual Fund Advertisement Through Content Analysis in Indian Mutual Fund Industry - K. Mohamed Jasim, Mr.; Afzalur Rahman, Dr. (International Journal of Engineering and Technology, 2018)
The survey and content analysis try to understand the investorâ€™s perception towards the content and information in the mutual fund advertisement. A sample of 926 investorâ€™s are participated in the survey. The structured questionnaire was taken respondent and answers are following questions. The questionnaire was structure like demographic questions, Content analysis ranking variables and feature and information requirement of mutual fund advertisement. 56% of the respondents participated in the Survey are male. 36% of the mutual funds are in the age group of 33 to 39 age. There is correlation between the income level and education of the mutual fund investor in the sample. Ranking analysis was conducted in the features of Advertisement and its presence in the mind of the investor. Emotional appeal and celebrity endorsement are the taking lead in the ranking list. Large visuals and USP are the next to ranked area in the mutual fund advertisement industries.Â Â